PEMBUKTIAN TERHADAP UNSUR KERUGIAN KEUANGAN NEGARA PADA KASUS TINDAK PIDANA KORUPSI - Ilhamdi Arfan; Erdianto '; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
National Development aims to realize the Indonesian people as a whole and the Indonesian community as a whole that is just, prosperous, and orderly based on Pancasila and the 1945 Constitution. To realize the just, prosperous and prosperous Indonesian society, its necessary to continually improve the efforts prevention and eradication of criminal acts on general and criminal acts of corruption in particular. Amid the national development efforts in various fields, the aspirations of the people to eradicate corruption and other forms of irregularities are increasing, because in the reality of corrupt deeds have caused huge losses of the state which in turn can have an impact on the emergence of crises in various fields. The purpose of this thesis is to know how to prove the element of state financial losses in cases of corruption and what is the basis of consideration in determining the state financial losses in cases of corruption.This research is a normative research or literature research, which is the type of research conducted by examining secondary legal materials or research based on book rules that have been recorded, also called library research. In this case the writter focus on research on the principle of law, by tracing the various regulations that have to do with the proof of the element of state financial losses in cases of corruption.From the results of the research that the writter do can be concluded, the first proof of the element of state financial losses has been started since the investigation where the investigator asked the expert to conduct an investigative audit and produce investigative audit results, the results are used in the trial contained in the indictment, although the investigative audit carried out independently and objectively the judge did not have to follow the amount of financial loss of the state calculated by the expert. The judge determines the amount of financial loss of the state based on the facts revealed in assembly, this is in accordance with the duties of the judge who are obliged to maintain the independence of the judiciary, but the difference in the calculation of state losses affects the return of the state financial losses that are not maximal due to corruption. The second basic considerations in calculating the state financial losses made by experts based on investigative audit while judge based on facts revealed in the trial. The difference in the calculation of state financial losses caused by the different methods of calculating state financial losses, although the source of financial loss is the same.Keywords: Proof - Finance - Country – Corruption